Search 75,412 tutors
FIND TUTORS
Ask a question
0 0

can you please factor out -12x^5+4x^4+4x^2

Tutors, please sign in to answer this question.

2 Answers

If the problem were to factor g(x) = –15x^6 + 5x^4 + 3x^2:

g(x) = –15x^6 + 6x^4 + 3x^2

g(x) = –3x^2(5x^4 – 2x^2 – 1)

h(x) = 5x^4 – 2x^2 – 1

h(x) = 5(x^2)^2 – 2(x^2) – 1

x^2 = (- -2 ± √(4-4(-5)) )/(2*5)

x^2 = (2 ± 2√(1+5) )/(2*5)

x^2 = (1 ± √(6) )/5

x = ± √( (1 ± √(6) )/5 )

g(x) = –3x^2(x ± √( (1 ± √(6) )/5 ) )

g(x) =
–3x^2
* (x – √( (1 + √(6) )/5 ) )
* (x + √( (1 + √(6) )/5 ) )
* (x – √( (1 – √(6) )/5 ) )
* (x + √( (1 – √(6) )/5 ) )
notice that what each term has in common is a factor of 4x2
 
so you get 4x2(-3x3 + x2 + 1)
 
you can check it by distributing the 4x2 back into the (-3x3 + x2 + 1)
 
 
another way of looking at it, if it helps, is once you realize that each term has a 4x2 as a factor, then you divide each term by 4x2 which is how you then get the other factor of (-3x3 + x2 + 1)

Comments

Hi Cameron;
I agree with your answer.  My guess is that the parenthetical expression must be factored again.  This is why I asked Bryce if he copied this exactly right.
I see what you mean. Its difficult sometimes because the questions asked on here don't give all the context in which they are being asked.